The semantic field of the core-lexeme of the - Adilkhanyan, Anahit (Bulletin of Yerevan University B: Philology, 2021)
The semantic field is a set of lexical units. Uniting into a core based on semantic and functional features. All lexical units join in each other in different kinds of semantic relations, which are formed in relation to its core-lexeme of the «eye» . Our task is to determine: 1) the field approach in the centre of which the nucleus (eyes) was given, 2) those meanings of the lexeme (eyes) that are reflected in the dictionary, 3) those phraseological units that express the tradition of our people as a carrier of a certain culture, 4) figurative meaning of the lexeme (eyes), 5) nonverbal meaning of the lexeme (eyes) as a means of communication.